Seasonal Variations in the Biodiversity, Ecological Strategy, and Specialization of Diatoms and Copepods in a Coastal System With Phaeocystis Blooms: The Key Role of Trait Trade-Offs - Breton, Elsa; Christaki, Urania; Sautour, Benoit; Demonio, Oscar; Skouroliakou, Dimitra-Ioli; Beaugrand, Gregory; Seuront, Laurent; Kléparski, Loïck; Poquet, Adrien; Nowaczyk, Antoine; Crouvoisier, Muriel; Ferreira, Sophie; et al. (Frontiers in Marine Science, 2021)
Although eutrophication induced by anthropogenic nutrient enrichment is a driver of shifts in community composition and eventually a threat to marine biodiversity, the causes and consequences on ecosystem functioning remain greatly unknown. In this study, by applying a trait-based approach and measuring niche breadth of diatoms and copepods, the drivers and underlying mechanisms of the seasonal species succession of these ecological communities in a coastal system dominated in spring by Phaeocystis blooms were explored. It is suggested that the seasonal succession of diatoms and copepods is the result of several trade-offs among functional traits that are controlled by the seasonal abiotic and biotic pressure encountered by the plankton communities. The results of this study highlight that a trade-off between competition and predator, i.e., weak competitors are better protected against predation, plays an important role in promoting plankton species richness and triggers the Phaeocystis bloom. As often observed in eutrophicated ecosystems, only the biotic homogenization of the copepod community and the shift in the diet of copepods toward Phaeocystis detrital materials have been detected during the Phaeocystis bloom. The diatom and copepod communities respond synchronously to fluctuating resources and biotic conditions by successively selecting species with specific traits. This study confirms the key role of competition and predation in controlling annual plankton succession.